SAPHO syndrome complicated by IgG4-related ophthalmic disease: a case report and literature review - Liu, Chenxiao; Chen, Tingting; Wang, Yanyan; Wang, Qi; Hu, Hao; Chen, Huanhuan (Frontiers in Immunology, 2025)
IntroductionSynovitis, acne, pustulosis, hyperostosis, and osteitis (SAPHO) syndrome is an extremely rare condition with nonspecific clinical signs and symptoms.Case descriptionHere, we present the case of a 54-year-old Chinese woman with an 8-year history of recurrent furuncles and a 6-year history of clavicular pain. Initially, computed tomography (CT) showed nonspecific changes. The patient was treated with nonsteroidal anti-inflammatory drugs for symptomatic relief; however, clavicular symptoms recurred intermittently. Two years before the current presentation, the patient experienced ocular discomfort from bilateral lacrimal gland enlargement and extraocular muscle thickening. She exhibited elevated IgG4 levels and was diagnosed with IgG4-related ophthalmic disease. Treatment with low-dose glucocorticoids slightly improved her clavicular symptoms. However, over the past month, her clavicular pain worsened. Recent CT and magnetic resonance imaging revealed a deformity of the right clavicular cortex near the end, with poor bone quality and continuity, and bone scintigraphy revealed intense radiotracer uptake in the sternoclavicular region. Consequently, the patient was diagnosed with SAPHO syndrome.ConclusionWhile clinical manifestations and imaging are helpful in narrowing the differential diagnosis, biopsy and histopathological examinations are necessary to confirm SAPHO syndrome. Regulation of TNF-α may be a therapeutic option for bone pain in this patient. In patients with an initial presentation of abnormal IgG4 levels, physicians must maintain a high index of suspicion to ensure appropriate treatment.